Gaseous mediators (H2S, NO and CO) a new approach in gastrointestinal protection - Pineda-Peña, Elizabeth Arlen; Chávez-Piña, Aracely Evangelina (Mexican Journal of Medical Research ICSA, 2023)
Gastrointestinal damage is generated by a wide range of harmful agents, and is the result of the activation of inflammatory, oxidant and cytotoxic mechanisms, that together overwhelm the “mucosa defense” of the gastrointestinal (GI) tract. It is currently known that the mechanisms by which gastric damage is generated are slightly different from those that generate intestinal damage. The treatments available on the market such as citoprotectors, the use of selective Ciclooxigenase 2 (COX-2) inhibitors, the co-prescription of acid suppressive agents and the use of prostaglandin analogues are mainly focused on the mechanisms of gastric damage, and their use has begun to be limited due to its adverse effects at intestinal and cardiovascular level. Due to its multifactorial origin, the prevention and treatment of GI damage requires effective therapies that can protect both gastric and intestinal level modulating more than one mechanism. Recently, has been reported the contribution of gaseous mediators nitric oxide (NO), hydrogen sulfide (H2S) and carbon monoxide (CO) in many physiological processes in the gastrointestinal tract, including the maintenance of GI mucosal barrier integrity. Experimental evidence has shown promising results regarding the gastric safety of these gasotransmitters, especially those coupled to NSAIDs. This review will try to give a general overview of the mechanisms of gastric and intestinal damage, their main differences, the existing therapies for their treatment and the information available on gas transmitters with a brief description of roles of each of these gaseous molecules.